2011
DOI: 10.1055/s-0031-1300512
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Activity of 2-Acyl-5(3)-hydroxytetrahydro-1H-pyrazole Derivatives

Abstract: The anti-inflammatory effects of five pyrazolidine derivatives on white mice and laboratory rats were studied using models of thermal aseptic inflammation and inflammation induced by injection of carragenin and histamine, as well as models of "cotton-ball granuloma" and epinephrine (adrenaline)-induced pulmonary edema. These effects were compared with those of the most commonly used non-steroid anti-inflammatory drugs, such as phenylbutazone (CAS 50-33-9) and diclofenac (CAS 15307-79-6). It was found that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Thus, they can be used as intermediates undergoing a subsequent reaction with hydrazine hydrate affording pyrazoles/pyrazolines. It has been reported that pyrazolines possess analgesic, anti-inflammatory [ 22 , 23 , 24 ] and antimicrobial activities [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they can be used as intermediates undergoing a subsequent reaction with hydrazine hydrate affording pyrazoles/pyrazolines. It has been reported that pyrazolines possess analgesic, anti-inflammatory [ 22 , 23 , 24 ] and antimicrobial activities [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazole and its derivatives are an important class of compounds and attracted widespread attention because of their pharmacological properties, been reported to have a large spectrum of biological effects (antidepressant, anxiolytic, antiallergenic, antihypertensive, hypoglycemic, insecticidal, and fungicidal), currently, certain pyrazole derivatives being extensively employed as pharmaceuticals. The speciality literature mentions several pyrazole compounds with analgesic (Amir and Kumar, 2005), anti-inflammatory (Zelenin et al, 1999), and antimicrobial activities (Akihiko et al, 2005;Bildirici et al, 2008;Goda et al, 2003;Korgaokar et al, 1996, Nauduri and Reddy, 1998, Susant et al, 2007Udupi et al, 1998). Some pyrazole derivatives have the advantage of possesing all these three actions (Adnan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The dosage volume was 20 mL/kg, with 10 animals per group (all males) maintained in a single cage. In experiment 4, the cotton ball-induced granuloma model in rats was established ( Yang et al, 2009 ; Efimova et al, 2010 ; Zelenin et al, 2011 ; Wang et al, 2016 ) (rats were anesthetised via intraperitoneal injection of 20% urethane solution (0.6 mL/100 g), a 0.5 cm incision made in the abdomen, and a 20 mg sterile cotton ball implanted under the skin of the right groin, following which the incision was sutured and disinfected). Rats were divided into model control (normal saline), prednisone acetate control ( Ma et al, 2016 ) (0.005 g kg –1 d –1 ), low-dose ZXZTCs (0.1313 g kg –1 d –1 ), medium-dose ZXZTCs (0.2625 g kg –1 d –1 ), and high-dose ZXZTCs (0.5250 g kg –1 d –1 ) groups.…”
Section: Methodsmentioning
confidence: 99%